A Low Cost Single-Switch Bridgeless Boost PFC Converter - Younghoon Cho (Institute of Advanced Engineering and Science, 2014)
This paper proposes the single-switch bridgeless boost power factor correction (PFC) converter to achieve high efficiency in low cost. The proposed converter utilizes only one active switching device for PFC operation as well as expecting higher efficiency than typical boost PFC converters. On the other hand, the implementation cost is less than traditional bridgeless boost PFC converters, in where two active switching deivces are necessary. The operational principle, the modeling, and the control scheme of the proposed converter are discussed in detail. In order to verify the operation of the proposed converter, a 500W switching model is built in PSIM software package. The simulation results show that the proposed converter perfectly achieves PFC operation with only a single active switch.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5558